2022
DOI: 10.3390/ijerph19148422
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Representations of the Aid That Public Psychological Support Points Provide to Adolescent Female Victims of Gender-Based Violence: Reformulation of Policies and Practices

Abstract: Gender-based violence in adolescence has become a social health problem that is creating great concern and interest worldwide. In this regard, knowledge of the role taken by the professionals responsible for screening, detecting, referring, and caring for adolescent victims is essential to be able to understand the phenomenon and its characteristics in a practical way. In this sense, psychologists specialising in the care of victims of adolescent gender-based violence have complete and in-depth knowledge, not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The aggressions that girls commit towards their partners would not have such a marked need for moral justification since girls might see them as a right that they have in a social context of false empowerment [65,66], which places women in the same position as men. In this way, adolescent girls seem to tend to repeat the same type of maladjusted behaviour that they see in their aggressive partners, and this is a factor that fosters an increase in mutual aggression in adolescent dating relationships [20]. Similar results have been suggested in the contexts of bullying and cyberbullying in which victims of school violence tend to become aggressors in cyberspace, understanding these behaviours as a fully justified form of revenge [67][68][69] that provides some degree of compensation [70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aggressions that girls commit towards their partners would not have such a marked need for moral justification since girls might see them as a right that they have in a social context of false empowerment [65,66], which places women in the same position as men. In this way, adolescent girls seem to tend to repeat the same type of maladjusted behaviour that they see in their aggressive partners, and this is a factor that fosters an increase in mutual aggression in adolescent dating relationships [20]. Similar results have been suggested in the contexts of bullying and cyberbullying in which victims of school violence tend to become aggressors in cyberspace, understanding these behaviours as a fully justified form of revenge [67][68][69] that provides some degree of compensation [70].…”
Section: Discussionmentioning
confidence: 99%
“…For example, research conducted by the Spanish Government on violence in adolescent couples in 2015 revealed that both boys and girls tend to accept a certain degree of control by their partner [17], and this is also a common fact among adult couples [18,19]. Psychologists specialized in caring for adolescent girls victimized in a dating relationship point out that these young women often recognize that they perpetrate or have perpetrated aggression (especially control) towards their partners, largely copying the type of behaviour that boys display towards them [20].…”
Section: Introductionmentioning
confidence: 99%